NEK1 variants confer susceptibility to amyotrophic lateral sclerosis - Kenna, P; van Doormaal PTC, P; Dekker, A; Ticozzi, N; Kenna, B; Diekstra, F; van Rheenen, W; van Eijk, K; Jones, A; Keagle, P; Shatunov, A; Sproviero, W; et al. (Nature Publishing Group, 2016)
To identify genetic factors contributing to amyotrophic lateral sclerosis (ALS), we conducted whole exome analyses of 1,022 index familial ALS (FALS) cases and 7,315 controls. In a novel screening strategy, gene burden analyses trained with established ALS genes revealed a significant association between loss of function (LOF) NEK1 variants and FALS risk. Independently, autozygosity mapping of an isolated community in the Netherlands revealed an NEK1:p.R261H variant as a candidate risk factor. Replication analyses of sporadic ALS (SALS) cases and independent control cohorts confirmed significant disease association for both p.R261H (10,589 samples analyzed) and NEK1 LOF variants (3,362 samples analyzed). In total, NEK1 risk factors are observed in nearly 3% of ALS cases. NEK1 has been linked to several cellular functions including cilia formation, DNA damage response, microtubule stability, neuronal morphology and axonal polarity. Our results provide new and important insights into ALS etiopathogenesis and genetic aetiology.